Magnetocoupling and domain structure of BiFeO3/ LaFeO3 heterostructures deposited on LaSrCoO3/Pt/TiO2/SiO2/Si (100) substrates by the soft chemical method - Deus, R. C. [UNESP]; Gonçalves, L. F. [UNESP]; Cavalcanti, C. C. [UNESP]; Rocha, L. S.R. [UNESP]; Longo, E. [UNESP]; Simões, A. Z. [UNESP] (Springer Nature, 2017)
BiFeO3 (BFO) and LaFeO3 (LFO) heterostructures were obtained at room temperature on Pt/TiO2/SiO2/Si (100) substrates by chemical solution deposition at a temperature of 500 °C for 2 h. For comparison, the films were also deposited on La0.5Sr0.5CoO3 coated Pt/TiO2/SiO2/Si (100) substrates. The magnetoelectric coefficient measurement was performed to show magnetoelectric coupling behavior of such heterostructures. La0.5Sr0.5CoO3 (LSCO) bottom electrode strongly promotes the formation of high intensity (104) texture of BFO-LFO heterostructures resulting in huge crystal size. The dielectric constants of the films increased from 307 to 400 at 1 MHz with the bottom electrode while the leakage current behavior at room temperature of the films decreased from 10 to 10–10−7 A/cm2 at a voltage of 5 V. Improvement of the P–E hysteresis loop was observed for the heterostructure due the decrease of leakage current caused by the LFO sublayer. Room temperature magnetic coercive field measurements indicate that the magnetic behavior is influenced by the nature of bottom electrode.